Le culte du macaron. Un nouveau genre, une nouvelle sociabilité, une nouvelle vitrine ? - Barbara Sémel (Itinéraires)
Women’s blogs and magazines have obvious generic links; they share, amongst other things, their editorial lines, visual aspects and readerships. What women’s magazines enunciate on paper is represented online in women’s blogs, using different temporal and technical variables which encourage interaction and rapidity of diffusion. How does a sociability of interactions, regulated by its own codes and customs and resting on a multi-layered system of complex exchanges, take shape in this girly blogosphere?